2017
DOI: 10.1158/1078-0432.ccr-16-2677
|View full text |Cite
|
Sign up to set email alerts
|

Timing of PD-1 Blockade Is Critical to Effective Combination Immunotherapy with Anti-OX40

Abstract: Purpose Antibodies specific for inhibitory checkpoints PD-1 and CTLA-4 have shown impressive results against solid tumors. This has fueled interest in novel immunotherapy combinations to impact patients who remain refractory to checkpoint blockade monotherapy. However, how to optimally combine checkpoint blockade with agents targeting T cell costimulatory receptors such as OX40 remains a critical question. Experimental Design We utilized an anti-PD-1 refractory, orthotopically-transplanted MMTV-PyMT mammary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
183
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(216 citation statements)
references
References 59 publications
(64 reference statements)
16
183
4
Order By: Relevance
“…30 Combining immunomodulating strategies could increase the proportion of responders, provided that the optimal timing of combination is choosen. 31 , 32 Our study shows that when combining OX40 engagement with an adjuvanted cancer vaccine opposite results can be obtained depending on timing of OX40 triggering. OX40 is therefore emerging as a relevant tuning molecule that might make the difference in combination therapies in either a positive or negative way.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…30 Combining immunomodulating strategies could increase the proportion of responders, provided that the optimal timing of combination is choosen. 31 , 32 Our study shows that when combining OX40 engagement with an adjuvanted cancer vaccine opposite results can be obtained depending on timing of OX40 triggering. OX40 is therefore emerging as a relevant tuning molecule that might make the difference in combination therapies in either a positive or negative way.…”
Section: Resultsmentioning
confidence: 77%
“…OX40 is therefore emerging as a relevant tuning molecule that might make the difference in combination therapies in either a positive or negative way. 32 , 33 The negative interference observed with OX40 triggering concomitant with cancer vaccine suggests that preclinical models should be thoroughly interrogated before planning clinical trials of combined approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Two different studies reported that the concurrent addition of a-PD-1 mAb markedly reduced the therapeutic response of a-OX40 mAb. 23 Further, another study that tested the combination of a-4-1BB and a-PD-1 antibodies in a murine spontaneous B-cell lymphoma model found that simultaneous use of a-PD-1 mAb diminished the antitumor activity of a-4-1BB mAb alone. However, this improved effect was not observed when a-PD-1 mAb was administered before a-OX40 mAb, highlighting the importance of timing and sequence of such treatments.…”
Section: Using Immunomodulatory Antibodies To Enhance Car T-cell Antimentioning
confidence: 99%
“…22 However, more recently other studies have reported opposing effects. 23,24 Interestingly, however, a study by Messenheimer et al found that when a-OX40 and a-PD-1 antibodies were administered sequentially by treating MMTV-PyMT tumor-bearing mice with a-OX40 mAb before a-PD-1 mAb, the sequential combination therapy resulted in augmented antitumor efficacy. 23,24 Interestingly, however, a study by Messenheimer et al found that when a-OX40 and a-PD-1 antibodies were administered sequentially by treating MMTV-PyMT tumor-bearing mice with a-OX40 mAb before a-PD-1 mAb, the sequential combination therapy resulted in augmented antitumor efficacy.…”
Section: Using Immunomodulatory Antibodies To Enhance Car T-cell Antimentioning
confidence: 99%
“…For example, in preclinical studies, OX40 stimulation has been demonstrated to enhance antitumor effects when combined with multiple therapeutic strategies including cytokines (Redmond, Triplett et al., 2012, Ruby, Montler et al, 2008), adjuvants (Gough, Crittenden et al., 2010, Houot and Levy, 2009, Voo, Foglietta et al, 2014), vaccinations (Murata, Ladle et al, 2006), chemotherapy (Hirschhorn-Cymerman, Rizzuto et al, 2009), or radiotherapy (Young, Baird et al., 2016). In addition, anti-OX40 antibodies have been combined with immunomodulatory antibodies against other costimulatory receptors (Lee, Myers et al, 2004, Morales-Kastresana, Sanmamed et al, 2013, Pan, Zang et al, 2002), or blocking coinhibitory pathways (Linch, Kasiewicz et al, 2016, Messenheimer, Jensen et al, 2017, Redmond, Linch et al, 2014) to treat lymphomas, sarcomas, colon metastases, and spontaneous hepatocellular carcinoma.…”
Section: Ox40mentioning
confidence: 99%